Desarrollo de un prototipo de control para el tratamiento de aguas residuales domésticas en el Laboratorio de Aguas y Aire de la Carrera de Ingeniería Ambiental - Campus Sur - Guerra Machado, Jhonny Xavier (2016)
Environmental Engineering at the Universidad Politécnica Salesiana Campus-Sur has a low volumetric capacity chemical reactor in its laboratories. For this reason, is necessary to build a higher volumetric capacity chemical reactor in order to students can to their practices in the best way. In an effort to get the variables involved such as temperature pH, level and conductivity it is necessary to use an Arduino Mega platform besides HMI programmed in the Labview software in which it is displayed and controls the parameters needed for water treatment. This system is connected whit a source power of three outputs 24, 12 y 5 volts, which it will energize to the different kinds of sensors and actuators in the process. Also, it has an aeration and agitation system. Besides, it has three auxiliary tanks of compounds like acid injections, bases, flocculants and chlorine, that when their mixed with the water to be treated change the properties. To end the reactor tank, move to Environmental Engineering Laboratories, and we will do the test in order to check correct operations of all the system involved in the reactor and that it meets all objectives.